Enhancing the Visibility of Traditional Craft Puspa Rinengga Batik Through Online Marketing Approaches - Savitri, Mimi; Cholsy, Hayatul; Hasanah, Uswatun (ASEAN Journal of Community Engagement, 2024)
This study addresses the visibility of traditional craft and focuses on developing a strategy to increase its exposure through online marketing platforms. Puspa Rinengga Batik Studio, a small and medium-sized enterprise in Sleman, Yogyakarta, Indonesia, specializes in creating batik with jangkang motifs. Despite their unique craft, the studio struggled with marketing their products, resulting in an imbalance between production and sales. This study explores a strategy to boost sales by leveraging social media for digital marketing. The approach involves empowering the community through workshops and implementing a sustainability program. As a result of this initiative, the studio successfully utilized social media to showcase its batik products to a broader audience, leading to a triple increase in sales. This study demonstrates that strategizing the visibility of traditional craft means popularizing the craft and improving the welfare of the studio’s members, particularly women, reinforcing the local cultural identity, and preserving batik as a cultural heritage.